Submission Workflow in OJS 3 - Stevens, Amanda (PKP Barcelona 2019 Workshop, 2019)
All users see the same interface, with more or less content depending on their role Each stage of the workflow is distinct - Submission, Review, Copyediting, Production Can easily skip a stage of the workflow Search and filter submissions Editors can access Metadata, Editorial History, and Submission Library at any stage Must assign editor to see editorial decision options Can assign editors to sections